Populasi Hewan Yang Terdapat Di Obyek Wisata Medan Zoo Simalingkar, Kab. Deli Serdang - Wardani, Sarwinda Kusuma; Siti, Fatimah; Evaronika Br, Tarigan; Saroh Madona, Sihombing (Program Studi Magister Pengelolaan Sumberdaya Alam dan Lingkungan Universitas Almuslim, 2022)
The Medan wildlife park is one of the tourist attractions and places of educatiom for people in indonesia, especially in the city of Medan. Medan wildlife park is located in Medan Tuntungan District, Deli Serdang Regency. The purpose of this study was to determine the types of animals in the Medan zoo, the management of the Medan zoo, and to find out the feed given to the animals at the Medan zoo. The method used in this research is the method of qualitative analysis. The result of this study indicate that the types of animals in the Medan zoo are generally 3 classes of animals identified, namely 17 species of mammals, 13 species of aves, and 4 species of reptiles, with food groupings namely omnivores, carnivores, and also herbivores. The conclusion of this study is that there are 3 classes of animals in which there are 34 species with a total population of 245 animals.